2009
DOI: 10.1007/s10875-009-9296-6
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling in the Aging Process

Abstract: Introduction The aging process represents a progressive decline in cellular and organism function. Explaining the aging process has given rise to a cornucopia for different theories in which the basic difference has been the question whether aging is genetically regulated or an entropic degeneration process. Discussion Different screening techniques have revealed that mammalian aging is associated with the activation of NF-κB transcription factor system. The NF-κB system is an ancient host defense system conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 98 publications
2
82
0
6
Order By: Relevance
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, since rapamycin is a strong immunosuppressive drug (408) that, on the one hand, inhibits type-1 IFN (41), modulates T cell trafficking (345), and regulates expression of Foxp3 in Tregs (138,326), but on the other, upregulates and improves the quality of CD8 memory T cell differentiation (13), it is not yet clear how this feeding regimen impacts immune senescence. Given the counter regulatory role of NFkB in inhibiting autophagy, a cross-talk between the inflammatory and autophagy pathway is likely to occur, since inducers of autophagy such as FOXO3a and sirtuin 1 (SIRT1) can inhibit NFkB signaling (28,(315)(316)(317)(318) and enhance autophagic degradation. Increased inflammatory responses observed during advanced age and increased inflammatory disease onset and progression during aging may well be an outcome of this cross-talk.…”
Section: H Autophagy Aging and Immune Responsementioning
confidence: 99%
“…13,14 Activated NF-kB translocation into the nucleus is associated with agerelated pathologies. 15 Previous studies showed that the transcriptional activity of NF-kB is regulated by SIRT6. SIRT6 can suppress the NF-kB activity by deacetylating the histone H3K9 of NF-kB dependent genes 16 as well as the Lys 310 (K310) of NF-kB p65 (RelA) subunit.…”
Section: Introductionmentioning
confidence: 99%